Estudos de complexos de rutênio (III) e complexos polímero-suportados em reações de hidrogenação e hidroformilação de substratos orgânicos - Rodrigues, Claudia (2014)
The synthesis and characterization of five ruthenium (III) complexes such as mer-[RuCl3(dppb)(N)], where N = pyridine and 4-substituted derivatives were performed in this work. These complexes were evaluated as catalysts in hydrogenation reactions of cyclohexene and some aldehydes. The obtained results were very satisfactory, presenting values higher than 80% of conversion, in 15 h. These ruthenium (III) complexes, two ruthenium (II) complexes containing CO as ligand and other four precursors, were also tested as catalysts in hydroformylation reactions of alkenes. Considering that is known that hydroformylation reactions can form several sub products, in the best reaction conditions, these catalysts were able to produce up to 61% of product, with only 14% of one sub product. These results were considered satisfactory, due to the possibility to work without additives, promoting a "green" reaction. The ruthenium (III) precursor mer-[RuCl3(dppb)(H2O)], was supported in three different polymers (poly-4-vinylpyridina P4VP, chitosan QT e aminopropyl silica APS). The catalytic activities of these polymersupported compounds were tested in hydrogenation of cyclohexene. Due to the possibility to separate the solid catalyst by filtration and easily isolate the product, the results showing 70% of conversion were considered satisfactory and "green". The ruthenium complex chitosan-supported was tested on the formation of a film, which was used to modify a glassy carbon electrode (GCE). This modified GCE was tested as an electrochemical sensor for the detection and quantification of drugs (acetaminophen and sildenafil citrate). The electrode showed a great electrochemical response and high sensitivity when compared to an unmodified glassy carbon electrode and a glassy carbon electrode chitosan modified. The polymeric film was stable to degradation in acids electrolytes showing a linear response evaluated in 1,25 x 10-5 a 4,99 x 10-4 mol L-1 concentration interval.